Estimating price sensitivity of economic agents using discontinuity in nonlinear contracts - Patrick L. Bajari; Han Hong; Minjung Park; Robert J. Town (Quantitative Economics, 2017)
This paper proposes a method to estimate price sensitivity of economic agents exploiting discontinuity in nonlinear contracts. As an application, we study contracts between a managed care organization and hospitals for organ transplants. Exploiting donut holes in the reimbursement contracts, we show that the impact of the reimbursement rate on hospitals' provision of health care services varies significantly across patients with different levels of illness severity. Our methodology is applicable to important classes of models such as consumer choice under nonlinear pricing and contracting with nonlinear incentives.
Keywords: C10; C51; I11; 330; Nonlinear contracts; heterogeneity in price sensitivity; health care